The Hydrophilic C-terminus of Yeast Plasma-membrane Na+/H+ Antiporters Impacts Their Ability to Transport K - Zimmermannová, Olga; Velázquez, Diego; Papoušková, Klára; Průša, Vojtěch; Radová, Viktorie; Falson, Pierre; Sychrová, Hana (Journal of molecular biology, 2024)
Yeast plasma-membrane Na+/H+ antiporters (Nha/Sod) ensure the optimal intracellular level of alkali-metal cations and protons in cells. They are predicted to consist of 13 transmembrane segments (TMSs) and a large hydrophilic C-terminal cytoplasmic part with seven conserved domains. The substrate specificity, specifically the ability to recognize and transport K+ cations in addition to Na+ and Li+, differs among homologs. In this work, we reveal that the composition of the C-terminus impacts the ability of antiporters to transport particular cations. In the osmotolerant yeast Zygosaccharomyces rouxii, the Sod2-22 antiporter only efficiently exports Na+ and Li+, but not K+. The introduction of a negative charge or removal of a positive charge in one of the C-terminal conserved regions (C3) enabled ZrSod2-22 to transport K+. The same mutations rescued the low level of activity and purely Li+ specificity of ZrSod2-22 with the A179T mutation in TMS6, suggesting a possible interaction between this TMS and the C-terminus. The truncation or replacement of the C-terminal part of ZrSod2-22 with the C-terminus of a K+-transporting Nha/Sod antiporter (Saccharomyces cerevisiae Nha1 or Z. rouxii Nha1) also resulted in an antiporter with the capacity to export K+. In addition, in ScNha1, the replacement of three positively charged arginine residues 539-541 in the C3 region with alanine caused its inability to provide cells with tolerance to Li+. All our results demonstrate that the physiological functions of yeast Nha/Sod antiporters, either in salt tolerance or in K+ homeostasis, depend on the composition of their C-terminal parts.
Keywords: Potassium; fungi; Na(+)-H(+) antiport; draslík; potassium homeostasis; Zygosaccharomyces; Lithium; Saccharomyces cerevisiae Proteins; C-terminus; Saccharomyces cerevisiae - proteiny; fungální proteiny; Fungal Proteins; Sodium-Hydrogen Exchangers; lithium; sodík; salt tolerance; Protons; cation/H(+) antiport; Sodium; protony